The tale of Peter Rabbit - Potter, Beatrix, 1866-1943. (Ashland, Ohio : Landoll, 1993)
Peter disobeys his mother by going into Mr. McGregor's garden and almost gets caught.
Has audio file on S drive
Keywords: Rabbits -- Fiction; Rabbits -- Fiction